Application of online UV absorption measurements for ozone process control in secondary effluent with variable nitrite concentration. (1st November 2016) - Stapf, Michael; Miehe, Ulf; Jekel, Martin
Abstract: Ozone process control in secondary effluent used for elimination of trace organic compounds (TrOCs) requires the use of surrogates, such as the relative reduction of UV absorption at 254 nm (ΔUVA254 ) to adapt the ozone dose to a varying water quality. In the present study, a closed-loop process control based on two online UVA254 measurements was successfully implemented and tested under realistic conditions with ozone doses from 0.2 to 1.05 mg-O3 /mg-DOC at a pilot scale ozonation system with subsequent coagulation filtration at a municipal wastewater treatment plant (DOC ∼ 13 mg/L, UVA254 ∼ 27 m −1, and nitrite peaks of up to 1.6 mg-N/L). It could be shown that measuring the UVA254 at the ozonation effluent was superior to the measurement of UVA254 at the filter effluent in terms of response time due to changes in water quality, whereas online measurement at the filter effluent showed a better agreement with laboratory data and a reduced maintenance interval due to less particles. Additional online nitrite measurement is not necessary as the ozone consumption by nitrite directly impacts ΔUVA254 . Graphical abstract: Highlights: Implementation of ozonation process control based on UVA254 abatement (ΔUVA254 ). Suitability of ΔUVA254 process control for tertiary ozonation was confirmed. ΔUVA254 process control compensates changes in ozone demand by e.g. DOC or nitrite. Measurement of ΔUVA254 allows an online estimation of achieved TrOC elimination.